KADAR IL-6 PLASMA PASIEN DIABETES MELITUS DENGAN DAN TANPA PENGIDAP RETINOPATI DIABETIKA (The Level of Interleukin-6 Plasma in Diabetes Mellitus Patients With and Without Diabetic Retinopathy) - I Wayan Putu Sutirta Yasa; I Nyoman Wande; Ni Ketut Niti Susila; Putu Budhiastra; Cokorda Istri Dewiyani Pemayun; Sianny Herawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Diabetic retinopathy is a complication of diabetes mellitus in the form of microvascular (aneurysma) which can cause blindness.Interleukin-6 is a pro - inflammatory cytokine produced by monocyte macrophage in the early inflammation. Chronic inflammationplays the role on artherosclerosis event, because it is directly correlated with all phases of it and cardiovascular disease as well. Theaim of this study is to know the difference in plasma IL-6 levels among patients suffering from diabetes mellitus together with diabeticretinopathy and without diabetic retinopathy. This study is an observational analytical research with cross sectional design. The sampleswere taken randomly as many as 16 patients, divided in each group suffering from or without retinopathy. The diabetic mellitus patientswere established through their related history and were examined randomly for blood glucose and their fundus or retinal abnormality.The level of IL-6 was examined by ELISA method with double antibody sandwich streptavidin - biotin. Based on this study it was foundthat the mean plasma levels of interleukin 6 (IL-6) of the diabetic mellitus patients with retinopathy was 1.165 ± 0.296 pg/mL andthe mean plasma levels of IL-6 with diabetes mellitus without retinopathy was 0.879 ± 0.230 pg/mL. Based on the normality test withShapiro-Wilk the data showed a normal distribution (p>0.05), while the Levene’s homogenity test obtained homogeneous with p= 0.369(p>0,05). The statistical analysis with two independent samples t-test showed that there were significant differences between the groupsof patients who suffered diabetes mellitus with retinopathy and without retinopathy (p=0.005). It can be concluded so far that the meanlevels of interleukin-6 (IL-6) plasma in diabetic mellitus patients with retinopathy is higher compared to patients with the same diseasebut without retinopathy.